Trs20 is Required for TRAPP II Assembly - Taussig, David (2013)
The modular TRAPP complexes act as nucleotide exchangers to activate the Golgi Ypt/Rab GTPases, Ypt1 and Ypt31/Ypt32. In yeast, TRAPP I acts at the cis-Golgi and its assembly and structure are well characterized. In contrast, TRAPP II acts at the trans-Golgi and is poorly understood. Especially puzzling is the role of Trs20, an essential TRAPP I/II subunit required neither for the assembly of TRAPP I nor for its Ypt1-exchange activity. Mutations in Sedlin, the human functional ortholog of Trs20, cause the cartilage-specific disorder SEDT. Here we show that Trs20 interacts with the TRAPP II-specific subunit Trs120. Furthermore, the Trs20-Trs120 interaction is required for assembly of TRAPP II and for its Ypt32-exchange activity. Finally, Trs20-D46Y, with a single-residue substitution equivalent to a SEDT-causing mutation in Sedlin, interacts with TRAPP I, but the resulting TRAPP complex cannot interact with Trs120 and TRAPP II cannot be assembled. These results indicate that Trs20 is crucial for assembly of TRAPP II, and the defective assembly caused by a SEDT-linked mutation suggests that this role is conserved.